The effect of Rehabilitation Exercises and the Use of the T.E.N.S. Device in Improving Functional Efficiency and Some Neurological Variables of the Knee Joint After Surgical Intervention of the Anterior Cruciate Ligament in Advanced Athletes - Rashid, Sinan Hisham; Hazim, Ola Sabri; Fadhil, Mutasim Abdul Karim (Jurnal Pendidikan Kepelatihan Olahraga (Pejuang), 2025)
The study aimed to rehabilitate the injured person to play after the injury, and not undergoing rehabilitation is a big mistake, as the athlete's return and continuation of his training program will lead to aggravation of the injury. Therefore, rehabilitation must be carried out for the injured after surgical intervention and enable a healthy and safe return as soon as possible by finding solutions and how to direct the effect of exercises and therapeutic devices in a way that suits the muscle work and reaches the recovery stage as quickly as possible. The study sample consisted of 5 players who were intentionally selected from advanced athletes in the sports of football, basketball, and weightlifting. who were injured with a torn anterior cruciate ligament and who underwent surgery, who were subjected to pre- and post (strength, range, balance, neurological variables) tests. The researchers concluded that the rehabilitation approach using rehabilitation exercises and the (TENS) device contributed to improving these variables. The researchers recommended paying attention to the experiences of academics and researchers specialized in sports rehabilitation and adopting a cooperation mechanism between the Ministry of Health and the faculties of physical education and sports sciences.